HistoGuide mobile application (virtual microscopy and slides): A quantitative usability pilot study - Zhong, Teoh Chern; Lee, Tien Tien; Mat Saad, Muhamad Ikhwan; Sagat, Mildred Paula; Jamaludin Khir, Nur Aqilah; Rajagopal, Thenmoliraj (Journal of ICT in Education, 2022)
HistoGuide application is a smartphone application system used by sixth-form students for virtual microscopy and slides to solve the problems of incorrect drawing and labelling, inability to apply magnification and scale, and inability to observe details in microscopic practical works. However, as a newly developed application, many still do not understand the usability of the HistoGuide application. In building a good application, one important part is good usability. Usability testing, especially in the HistoGuide application, can show users’ ease and efficiency in using the system. The authors try using the USE questionnaire with 33 respondents as a pilot study before a real one. The analysis resulted in an average value of the usefulness construct of 92.8%. Then, the construct ease of use with 92.4%, ease of learning with 92.4%, and satisfaction with 93.8%. These results indicate that the HistoGuide application is good. The results of measuring the usability of the HistoGuide application with the classification "High" to use, with a usability value of 92.8%. The results of usability measurement are expected to help develop and improve the HistoGuide application in the future to complement the conventional microscopic practicals works.